Investigation of Contaminated Bacteria and Some Toxic Elements of Groundwater in Some Wells in the Abu Ghraib Area/Baghdad - U. Hasan, Kareem; A. Hussain, Tariq (Iraqi Journal of Science, 2023)
A total of 50 wells water samples were collected from 10 wells in Abu Ghraib site/ Baghdad for detection of coliform, fecal coliformand and pseudomonas aeruginosa bacteria, and the pollution of toxic ions (No3-, B+3, pb+2 and Cd+2 ) in wells water. Results showed microbial pollution by coliform, fecal Coliform bacteria in wells water when using presumptive, confirmed and complete tests, P. aeruginosa bacterium was isolated and identificated on Cetrimide Agar media, estimated the Most Probable Number (MPN) of coliforms and P. aeruginosa, results showed difference in mean of (MPN) of wells water. Most of toxic ions concentrations were low comparing with the recommended hygienic standards from the World Health Organization (WHO). Wells water was contaminated by coliforms and P. aeruginosa bacteria that affected the quality, but chemical pollution don’t found in wells water because constrations of toxic ions lower them of (WHO) standards.